Optimal Control of a Viscous Shallow Water Equation - Wenbin Zhang; Jiangbo Zhou (Advances in Mathematical Physics)
This paper is concerned with a viscous shallow water equation, which includes both the viscous Camassa-Holm equation and the viscous Degasperis-Procesi equation as its special cases. The optimal control under boundary conditions is given, and the existence of optimal solution to the equation is proved.